Formaldehyde Adulteration in Meatball is Still Prevalent, and it is Hard to Identify Only from its Physical Properties - Yoga Pratama; Asri Astuti; Bhakti Etza Setiani (Journal of Applied Food Technology, 2023)
Human carcinogenic compound formaldehyde (alternative name, formalin) adulteration in food is inappropriate and illegal. However, its simple and cheap procedure in giving desired food preservation effect becomes the factor of its prevalence in Indonesian community. Our current study focuses on the usage of formaldehyde in meatball products which are sold in bulk without refrigeration in traditional market set up. Eighty different packages of meatballs were collected following accidental sampling method from small groceries in Tembalang, Semarang, Central Java in 2019. Samples were characterized for their formaldehyde content (AOAC 931.08), total plate count, moisture and organoleptic properties. Formaldehyde was found in 1 sample at the level of 176.2 ppm. Whereby, it was among only 4 % of samples that met the maximum microbial limit of 5 log CFU/g. The particular sample was characterized by pale color, rather slimy surface, chewy and weak meatball aroma. Note, this characteristic is not unique and is shared by several other samples. Therefore, this study brings an update that formaldehyde adulteration is still prevalent. The adulterated product has hardly distinctive sensorial properties which make self-evaluation difficult, thus exposing consumers to potential food safety risks.